PENGARUH FLUKTUASI NILAI TUKAR (KURS) RUPIAH TERHADAP PERGERAKAN HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Binsar Sihombing; hendra agustinus marbun (JAKPI - Jurnal Akuntansi, Keuangan & Perpajakan Indonesia, 2017)
This study is intended to determine the effect of exchange rate fluctuations (exchangerate) on stock price movement of manufacturing companies in BEI. The sample is the exchangerate of rupiah and stock prices in 2009. The data analysis technique used is a simple linearregression analysis. The results OF this study indicate that the appreciation of the rupiahexchange rate has a positive relationship to stock prices at manufacturing companies inIndonesia Stock Exchange